WOMEN'S ROLE IN STRENGTHENING RELIGIOUS ACTIVITIES THROUGH EMPOWERMENT OF THE HOUSE OF TAHFIZ DARUL JANNAH - Irwandi Irwandi; Zulamri Zulamri; Romi Maimori; Tri Yuliani (State Institute of Islamic Studies Batusangkar, 2021)
The role of women in Minangkabau plays a strategic place in fostering people, including in younger generation in